Republic of Togo Basic Agricultural Public Expenditure Diagnostic Review - World Bank (Washington, DC, 2014)
After 15 years of political stagnation due to political troubles from 1990 to 2005, Togo is now enjoying political stability and economical revival. Agricultural sector is doing especially well and the government is reviewing the public expenditures in this domain. The goal is to learn lessons from the past in terms of budget and to increase the performances of the programs to come. The objectives of this document are: a) better understand how the country is performing in agriculture; b) learn lessons from the past in terms of budgetary execution in agriculture to make new programs more effective; c) increase the knowledge of the government and his partners on their resources so they can make knowledgeable decisions regarding the agriculture budget; and d) contribute to the internalization of the review of public expenditures.